Application of Diversion to Children in Conflict with the Law as an Effort to Protect Children's Rights in Realizing Restorative Justice - Indira, Safira Prima; Lubis, Syofiaty (LEGAL BRIEF, 2024)
: This research aims to find out how the legal regulations regarding the implementation of diversion for children who are in conflict with the law are and to find out how diversion is implemented as an effort to protect children's rights in realizing restorative justice. The results of this research show that based on article 7 paragraph (2) of Law no. 11 of 2012 concerning the criminal justice system states that the right to diversion for children in conflict with the law can only apply to children who are 12 (twelve) years old and for crimes with a prison sentence of less than 7 years and not for repeat crimes. In terms of implementation, diversion is carried out through deliberations between the victim's family and the perpetrator's family, led by a diversion facilitator from a District Court judge who listens to claims for losses submitted by the victim's family. Furthermore, based on article 55 paragraph (1) government regulation no. 65 of 2015 concerning guidelines for implementing diversion states that if diversion deliberations reach an agreement then children in conflict with the law can be free from criminal punishment, however, in accordance with article 53 paragraph (2) Perma No. 4 of 2014 concerning Guidelines for implementing diversion states that if deliberations do not reach an agreement then the criminal case will be resolved through a juvenile criminal justice mechanism at court level